Evaluation of Different Planting Methods against Major Diseases of Selected Boro Rice Varieties (SAARC Journal of Agriculture, 2023)
The System of Rice Intensification (SRI), an innovation that was first emerged in Madagascar in the 1980s and has now diffused to more than 50 countries. The present study was conducted as field experiment in the central farm of Sher-e- Bangla Agricultural University (SAU) using RCBD design and the lab experiment was carried out in Molecular Biology and Plant Virology Laboratory under the Department of Plant Pathology, Sher-e-Bangla Agricultural University, Dhaka-1207. The experiment was carried out to adopt SRI as an alternative approach for management of major rice diseases in Bangladesh, during the period of November, 2020 to June, 2021. From the study it was revealed that all the selected planting methods gave the significantly effect on percent disease incidence (% DI) and severity (% DS) of major rice diseases viz. blast, brown spot, sheath blight and bacterial leaf blight in selected Boro rice varieties (BRRI dhan 28, BRRI dhan 89, BRRI dhan 92 and purple rice). The highest disease incidence and severity was recorded in conventional planting method and the lowest in basic SRI method. The moderate disease incidence and severity was recorded in modern SRI method which was statistically non-significant with Basic SRI method but significant with conventional method. However, it is necessary for further trial in different variety and AEZs as field experiment. So, it may be recommended that the System of Rice Intensification (SRI) may be alternative for management of major rice diseases.SAARC J. Agric., 21(1): 139-152 (2023)